Students’ Workplace Language Needs: Faculty of Science as an Example - Al-Jamal, Dina (DIRASAT: EDUCATIONAL SCIENCES, 2016)
The present study aimed at investigating the reasons behind faculty of science undergraduates’ English language learning along with identifying their most needed language skills. Further, it sought shedding light on undergraduates’ evaluation of the course merits for future job together with ascertaining their self confidence in job interviews. In order to achieve its objectives, the present study followed a descriptive research design; questionnaires and interviews which were developed by the researcher and then were checked for reliability and validity measures. The sample of the study consisted of 294 (150 male; 144 female) faculty of science undergraduates who responded to the survey questionnaire. Upon filling in the questionnaire, 30 students were interviewed. The findings of the study indicated undergraduates’ keenness to learn English for the reason that it will help them in their future career. The utmost, however, language surveyed need was listening as it helps them in their course of study. What’s more, the study reported that the instruction understudy is steered towards reading and grammar rather than communication language skills needed for workplace along with a nurture of self-confidence prospects.